Which Incentives Does Regulation Give to Adapt Network Infrastructure to Climate Change? - A German Case Study - Anna Pechan (University of Oldenburg, Department of Economics, 2014)
Climate change poses a new challenge in particular to long-lasting electricity networks. At the same time, this industry is highly regulated, which greatly affects the behavior of network operators. In this paper, the impact of regulation in general and of the German electricity grid regulation in particular on anticipatory adaptation investments is analyzed. The qualitative analysis shows that in general a whole set of elements of the regulatory model and their coordination influence the decision of ex ante adaptation to climate change. A careful and balanced design, e.g. of efficiency and quality measurement, is thus crucial to avoid inadequate adaptation. The regulation in Germany discourages flexible adaptation to extreme weather events (EWEs). For irreversible adaptation of new and existing infrastructure to EWEs, the incentives highly depend on the cost approval of the regulator. Currently, the regulation discourages this type of adaptation. But if the additional costs can be claimed, the network operator is indifferent to adapt. Similarly, incentives to irreversibly adapt existing and new infrastructure to slow onset events (SOEs) range between excessively high and undistorted depending on the regulator's discretion. Undistorted means that the decision to implement adaptation measures is not biased by regulation. Undistorted are also the incentives for flexible measures to adapt to SOEs. Only in the undistorted cases, the risk of inadequate adaptation are borne by the network operator.
Keywords: 330; Electricity Networks; Regulation; Climate Change; Germany